Iran Economic Monitor, Fall 2020 : Weathering the Triple-Shock - World Bank (World Bank, Washington, DC, 2021)
The Iranian economy entered a third consecutive year of recession following the triple-shock of sanctions, oil market collapse and Coronavirus (COVID-19). High inflation placed additional economic stress on lower income households following a sharp depreciation of the currency. As Coronavirus (COVID-19) cases surged, stricter measures were enforced in Fall 2020 and new social transfers were announced. This Iran Economic Monitor (IEM) provides an update on key economic developments and policies. It examines these economic developments and policies in a longer-term and global context, and assesses their implications for the outlook for the country. Its coverage has ranged from the macroeconomy to financial markets to indicators of human welfare and development. The Special Focus chapter of this report presents recent poverty figures and assesses the welfare and poverty impacts of the Coronavirus (COVID-19) pandemic in Iran.